MOTIVATION OF THE USE OF DIGITAL WALLETS IN YOUNG GENERATIONS IN THE TIME OF THE COVID-19 PANDEMIC - Herdioko, Jonathan; Titalessy, Pisi Bethania; Krisanta, Brigitta Evelyn (Archives of Business Research, 2021)
This study aims to analyze how the Technology Acceptance Model which consists of Percieved usefulness, Perceived Ease of use, Privacy and Security, and additional variable "Promotion Programs" affect behavior intention in using e-wallets or digital wallets in the current pandemic era. A total of 394 respondents aged 16-30 years old who use e-wallets in Yogyakarta were sampled in this study. The results using the SEM test show that perceived usefulness and behavioral intention have a significant effect. Meanwhile, Perceived Ease of use, Privacy and Security, and promotional programs are not significant on E-Wallets Usage.